PERBEDAAN TINGKAT KECEMASAN DAN DEPRESI MAHASISWA YANG TINGGAL BERSAMA ORANG TUA DAN TINGGAL SENDIRI - Annisa Biiznillah Utami; Jumaini Jumaini; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
University would only be found in certain area, that’s why there are student that lived far from their parents so they are vulnerable to anxiety and depression. The purpose of this study was to determine differences in anxiety and depression levels of students living with parents and themselves. This research used descriptive analytical method with cross sectional approach. The study was conducted on 82 respondents using a cluster sampling technique. The measuring instrument used was a questionnaire developed by the researcher that were valid and reliable test with cronbach alpha value 0.906 for the anxiety questionnaire and 0.907 for the depression questionnaire. The analysis used is univariate analysis with frequency distribution and bivariate analysis with Chi-square test. The results showed that majority of student lived alone experienced mild anxiety levels of 11 people (13.4%). At a moderate level, more anxiety is experienced by students living with parents, as much as 27 people (32.9%), and severe level experienced by students who live with parents is 6 people (7.3%). The level of mild depression was 40 people (48.8%) on students living with parents and 41 people (50.0%) in students living alone. The statistical test results showed that there were no differences in anxiety and depression levels of students living with parents and living alone with p value (0.792) <α (0.05) for anxiety levels and p value (1,000)> α (0.05) for level of depression. The results of this study are expected to be a reference in the development of knowledge about the difference levels of anxiety and depression of students living with parents and living alone.Keywords: Anxiety, Depression, Shelter, Students